Plan parcial de revitalización de la ronda del río Bogotá (Tibabuyes) (2022)
The Bogota River runs through the city in the western part, being taken as an edge of delimitation and separation with the surrounding municipalities, in the research conducted around the river water body were found problems such as pollution, settlements in the round, dumping, among others, which were evidenced in the northwestern area of the locality of Suba precisely in the local planning unit Tibabuyes.